El juego y la fuerza testimonial de la voz infantil en Cartucho y Desierto sonoro. - Paul Abeyta, Michael (Confluencia: Revista Hispánica de Cultura y Literatura)
The article focuses on the representation of the child’s voice in the works "Cartucho" by Nellie Campobello and "Desierto sonoro" by Valeria Luiselli, highlighting its testimonial value in the context of social conflicts. Both works use the child’s perspective to address the Mexican Revolution and the crisis of refugee children at the border between the United States and Mexico, showing how children's imagination challenges adult reality and provokes critical judgment in the reader. Through the playful experiences of children, themes of violence, injustice, and collective memory are explored, emphasizing the importance of their voice in contemporary narrative.